Solvability and nilpotency of expanded groups relative to the nearring of zero and congruence preserving functions. Issue 12 (2nd December 2022) - Peterson, Gary L.; Scott, Stuart D.
Abstract: In this paper we study solvability and nilpotency of an expanded group relative to the nearring of zero and congruence preserving functions of the expanded group. A particular case of interest is when the expanded group is a nearring module. This leads to consequences when an expanded group is viewed as a nearring module over its nearring of zero preserving polynomial functions.